‘That’s how you make the most out of a stay’: Positionings within, and perspectives on, the truly intercultural experience during study abroad - Lídia Gallego-Balsà (Sintagma, 2018)
Study abroad has traditionally been perceived as an opportunity for students to learn a foreign language by immersing themselves in the foreign language culture. However, students do so in very different ways. This paper examines how language instructors and international students at a university in Catalonia (Spain) project contrasting views of the ‘truly’ intercultural experience abroad and the importance that each group ascribes to learning the local language(s), Catalan and Spanish. The analysis leads to two main findings. The language instructors legitimise the experience of full immersion in the local culture as they believe that this contributes to the achievement of high levels of competence in local language(s). Nevertheless, their position stands in marked contrast to the experience of the international students, who tend to interact primarily with other international students as a result of the lack of opportunities that the local students offer them to enter local networks.